Access of Students with Disabilities to Educational Services in Jordanian Universities: Physical and Attitudinal Barriers and Challenges - Muhidat, Mohammad; Algolaylat, Ahmad; Alodat, Ali (Dirasat: Human and Social Sciences, 2021)
This study aimed to identify the level of educational services provided for students with disabilities in public universities, their attitudes towards these services, and the obstacles that they face. An educational services scale, which consists of (68) items distributed into seven main dimensions, was applied to (208) students with disabilities. The results indicated an average level of services and obstacles. The results also showed that there were statistically significant differences according to the gender and level of study variables. At the same time, there were no statistically significant differences due to disability and college types’ variables.